2019
DOI: 10.3390/cells8020181
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing Fluid Reflects the Inflammatory Nature and Aggressiveness of Breast Tumors

Abstract: Wound healing fluid that originates from breast surgery increases the aggressiveness of cancer cells that remain after the surgery. We determined the effects of the extent of surgery and tumor-driven remodeling of the surrounding microenvironment on the ability of wound-healing to promote breast cancer progression. In our analysis of a panel of 34 cytokines, chemokines, and growth factors in wound healing fluid, obtained from 27 breast carcinoma patients after surgery, the levels of several small molecules wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Similar experiments were also conducted by Agresti et al who confirmed that the composition of SWF depends not only on the type of surgical procedure (quadrantectomy, mastectomy), but also on the aggressiveness of the tumor (in situ vs invasive), molecular subtype (luminal vs. triple-negative), the size of the tumor, staging (G2 or G3), and lymph node status (positive or negative for cancer cells). They suggested that the composition of surgical wound fluids collected from the tumor bed of breast cancer patients reflects the inflammatory nature and aggressiveness of the breast tumor [8]. The authors analyzed a panel of 34 cytokines, chemokines, and growth factors in the SWF of breast cancer patients and found, that the concentrations of IP-10, IL-6, G-CSF, osteoponin, MIP-1 alpha, MIP-1 beta, and MCP1-MCAF were higher in more aggressive tumors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar experiments were also conducted by Agresti et al who confirmed that the composition of SWF depends not only on the type of surgical procedure (quadrantectomy, mastectomy), but also on the aggressiveness of the tumor (in situ vs invasive), molecular subtype (luminal vs. triple-negative), the size of the tumor, staging (G2 or G3), and lymph node status (positive or negative for cancer cells). They suggested that the composition of surgical wound fluids collected from the tumor bed of breast cancer patients reflects the inflammatory nature and aggressiveness of the breast tumor [8]. The authors analyzed a panel of 34 cytokines, chemokines, and growth factors in the SWF of breast cancer patients and found, that the concentrations of IP-10, IL-6, G-CSF, osteoponin, MIP-1 alpha, MIP-1 beta, and MCP1-MCAF were higher in more aggressive tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the major cytokines present in SWF after surgery, especially in patients after neoadjuvant chemotherapy [9]. Agresti et al also found a higher concentration of this cytokine in patients after radical mastectomy than in those after quadrantectomy [8].…”
Section: Rantesmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical excision of the primary tumor induces a wound healing response and inflammatory processes that alter the local environment and stimulate the growth kinetics of the remaining cancer foci, thereby potentially promoting metastasis [7][8][9]. Studies using global transcriptome analysis of a panel of triple-negative breast cancer (TNBC) cell lines have found that stimulation with surgical wound fluid (SWF) significantly increases the expression of genes related to wound response, cytokine activity, and locomotory characteristics [10].…”
Section: Introductionmentioning
confidence: 99%